Atención y memoria en estudiantes de básica primaria de instituciones públicas rurales de Boyacá, Colombia (2021)
Attention and memory are two closely related and parallel processes in child development. This study aimed to establish the relationship between attention and memory processes in children from rural schools with respect to age, gender and educational level. Fifty students were selected by random sampling within a descriptive correlational study. The Child Neuropsychological Assessment was used. The results showed significant differences regarding age for the memory and visual attention subtests. In the sex variable, no significant differences were found.Regarding the level of schooling, significant differences were found for the attention and memory subtests except for logical memory. In conclusión, lower performance was observed when compared to urban population scales.